IMPLEMENTASI DIRECT SELLING PADA PT.MELIA SEHAT SEJAHTERA - Feri Sulistyanto; Femi Oktaviani (MEDIAKOM : Jurnal Ilmu Komunikasi, 2020)
PT.Melia Sehat Sejahtera is a direct sales company with a multilevel marketing system established in 2003 with health and beauty products. Melia Sehat Sejahtera Company helps the economy of various groups by becoming a distributor or business partner. In the implementation of direct selling, communication becomes an important role in terms of persuading, inviting and influencing prospective consumers let alone a bad image of the multilevel marketing system. The form of communication, communication process, the choice of communication media and communication barriers in implementing direct selling are the objectives of the study. Qualitative research methods and case studies as the approach. Obtaining data through observation, interviews, researcher documentation and literature studies as a complement to the data. The results of this study indicate that the form of communication in the implementation of direct selling PT. MSS uses interpersonal communication, group communication, public communication and organizational communication as distributor activities to increase sales and maintain networks. The communication process used by distributors in direct selling is primary and secondary communication processes using symbols and other tools. Media communication in direct sales in the form of audio, audio visual, print and electronic. And barriers to communication in sales are caused by personal and environmental impacts on potential consumer decisions..